Elective genomic testing: Practice resource of the National Society of Genetic Counselors. Issue 2 (4th January 2023) - Blout Zawatsky, Carrie L.; Bick, David; Bier, Louise; Funke, Birgit; Lebo, Matthew; Lewis, Katie L.; Orlova, Ekaterina; Qian, Emily; Ryan, Lauren; Schwartz, Marci L. B.; Soper, Emily R.
Abstract: Genetic counseling for patients who are pursuing genetic testing in the absence of a medical indication, referred to as elective genomic testing (EGT), is becoming more common. This type of testing has the potential to detect genetic conditions before there is a significant health impact permitting earlier management and/or treatment. Pre‐ and post‐test counseling for EGT is similar to indication‐based genetic testing. Both require a complete family and medical history when ordering a test or interpreting a result. However, EGT counseling has some special considerations including greater uncertainties around penetrance and clinical utility and a lack of published guidelines. While certain considerations in the selection of a high‐quality genetic testing laboratory are universal, there are some considerations that are unique to the selection of a laboratory performing EGT. This practice resource intends to provide guidance for genetic counselors and other healthcare providers caring for adults seeking pre‐ or post‐test counseling for EGT. Genetic counselors and other genetics trained healthcare providers are the ideal medical professionals to supply accurate information to individuals seeking counseling about EGT enabling them to make informed decisions about testing and follow‐up.